Korelasi Skor Get with The Guidelines-Heart Failure dan Rasio Platelet Limfosit pada Pasien Rawat Inap dengan Gagal Jantung - Panjaitan, Samuel Hendryk; Dalimunthe, Naomi Niari; Supriatmo, Supriatmo; Pradana, Andika (UI Scholars Hub, 2024)
Introduction. The Get with the Guidelines-Heart Failure (GWTG-HF) risk score is a widely utilized and validated tool for assessing prognosis in patients with heart failure. Inflammation significantly contributes to the pathophysiology of heart failure, evidenced by platelet activation and a reduction in lymphocyte counts. Consequently, the platelet-to-lymphocyte ratio (PLR) may function as a prognostic biomarker in this population. This study aims to investigate the correlation between the GWTG-HF risk score and PLR as an inflammatory marker in patients hospitalized with heart failure. Methods. This cross-sectional study utilized medical records of heart failure patients admitted to Adam Malik Hospital in Medan from January 2022 to July 2023. Total GWTG-HF scores and PLR values were recorded at the time of patient admission. Correlation analyses were conducted to assess the relationship between the two variables. Results. The study evaluated 106 patient records, with male patients comprising 72.64% and a mean age of 55.84 (SD 14.09) years. The median GWTG-HF score was 37.5, while the median PLR was 137.14. Correlation analysis yielded a coefficient of r = 0.249 (p < 0.05), indicating a statistically significant association.Conclusion. A weak positive correlation exists between the GWTG-HF score and PLR in patients with heart failure, suggesting that PLR may serve as a supplementary inflammatory marker in prognostic assessments.